EDUCATIONAL AND ETHICAL VIEWS OF YUSUF KHAS HAJIB, MAHMUD KASHGARI, AND AHMAD YUGNAKI. KAYKAVUS’S "QABUSNAMA" AND THE EDUCATION OF NOBILITY (JUVONMARDLIK). - Abdulazizova , Pokiza; Yangiboyeva , Feruza (Journal of Pedagogical and Philological Research, 2026)
This article provides a scientific and theoretical analysis of the educational and ethical views of Eastern thinkers Yusuf Khas Hajib, Mahmud Kashgari, and Ahmad Yugnaki, as well as the issues of nobility (juvonmardlik) education presented in Kaykavus’s "Qabusnama." In the works of these scholars, issues such as human perfection, ethical purity, attitude toward knowledge, culture of conduct in society, respect for parents and teachers, diligence, honesty, and justice occupy a significant place. The article highlights the harmony between these ideas and their importance in today’s education and upbringing processes, illustrating the role of this heritage in raising the younger generation as well-rounded individuals.